If it's not what You are looking for type in the equation solver your own equation and let us solve it.
h in (-oo:+oo)
90 = (15/2)*h // - (15/2)*h
90-((15/2)*h) = 0
(-15/2)*h+90 = 0
90-15/2*h = 0 // - 90
-15/2*h = -90 // : -15/2
h = -90/(-15/2)
h = 12
h = 12
| 4(x+14)=60 | | 73/100*(-2/7) | | -3*-1-1=-1+-3 | | 16t+3=0 | | x=32-5t+2t^2 | | https://www.youtube.com/watch?v=UFLWvSRXNl4 | | 5d+2=37 | | z/5=334 | | -2(-6+5x)-1= | | 7(t-3)+7t=7(2t+3)-10 | | x-54/2=32/4 | | 5w^2-20= | | -3(6x+9)+1= | | x=12000(.04) | | 3(40+d)=4(37-d) | | 4x+4=2-1 | | 4x+b=2-1 | | 9=2b-12 | | 6(v-5)+6= | | 2x+25=31 | | 3lnx-ln32=lnx/2 | | .05(x)-.06(y)=-185 | | -6(-5-10k)= | | x^2(-2x-7)=0 | | 5(x+3)-10=2(x+31) | | 6x+27=-4x-3 | | (4y+4)-(2+3y)=5 | | 2(5x+3)=3x+20 | | -3x+8+5x=-4 | | x-8=80/10 | | 7(1-6p)= | | 2x+1=-4x-11 |